EFEK PELATIHAN LARI AKSELERASI DAN PELATIHAN LARI INTERVAL DI PANTAI BERPASIR DALAM MENINGKATKAN KEMAMPUAN ANAEROBIK, POWER OTOT TUNGKAI DAN KECEPATAN LARI 100 METER PADA SISWA KELAS X SMA NEGERI 1 SUELA LOMBOK TIMUR TAHUN PELAJARAN 2018/2019 - Evitamala, Lilik; Adiputra, I Nyoman; Ratna Sundari, Luh Putu; Handari Adiputra, Luh Made Indah Sri; Griadhi, I Putu Adiartha; Purnawati, Susy (Sport and Fitness Journal, 2019)
100 meters’ run is a short distance that someone has to run with repulsion as fast as possible up to distance 100 meters’. Become a good runner must have anaerobic capability, power of limb muscles. This research aims to find out the improvement of anaerobic capability, power of limb muscles and 100 meters’ running speed from the effect of training of acceleration running and interval running at sandy beach on tenth grade students at SMA Negeri 1 Suela in East Lombok. An experimental study of Pre-Post Test Control Group Design had been conducted on 30 students aged between 16-17 years old who had physical fitness level of medium or moderate. Samples were divided into two groups by using simple random allocation technique. Group I was given the training of acceleration running at sandy beach and group II was given the training of interval running at sandy beach. The average of anaerobic capability, power of limb muscles and 100 meters’ running speed on each group, has p < 0.05. It means that on each group, there is a meaningful and significant improvement change after training. It can be concluded that the training of acceleration running and interval running at sandy beach equally improving anaerobic capability, the power of limb muscles and 100 meters’ running speed. Key words: Acceleration running, interval running, anaerobic capability, power of limb muscles, 100 meters’ running.